Bone Development and Leg Problem Incidence in Four Strains of Turkeys - Eusebio-Balcazar, P.; Oviedo-Rondon , E.O.; Grimes, J.L.; Scott, J. (International Journal of Poultry Science, 2015)
Leg problems have become an increasingly prevalent issue in the turkey industry. The objective of this experiment was to evaluate leg bone development and growth and the incidence of leg problems in different strains of turkeys. Males from 4 Aviagen genetic lines, (A, B, C and D) were obtained and raised in 48 floor pens. Leg health issues were classified at 16 and 33 d and 15 and 18 wk of age. Weights and morphological measurements of the femur, tibia and tarsus-metatarsus were recorded at hatch and every two wk from two birds per strain and in poults with twisted legs at 16 d. At 20 wk bone mineral density (BMD) and content (BMC) of leg bones were obtained using DEXA. Weekly data were fitted to Gompertz equations and allometric ratios were calculated to assess bone development. Strain A turkeys had higher BW and femur weight at hatch than strain D toms. Strain A toms also had higher allometric growth ratios for all leg bones between 1 to 8 wk of age and lower tibia and femur BMD at 20 wk than strain D toms. At 16 d strain A turkeys had the highest incidence of twisted legs and strain A and C toms had higher incidences of crooked toes than strain D turkeys at 15 and 18 wk. Higher growth rates early in life may result in weaker bones that result in turkeys being more susceptible to developing leg problems. In summary, bone development patterns, BMD and incidence of leg problems vary in genetic lines of turkeys.